The Influence of Performance Therapy with Statins on Androgen Balance in Patients with Stable Angina in Combination with Type 2 Diabetes Mellitus - Kapustуnska O. (Львівський клінічний вісник)
Introduction. Since cholesterol is a substrate for the synthesis of sex hormones, including testosterone, changes in androgen availability in patients taking statins can be expected. At the same time, the effect of statins on androgenic provision of patients with coronary artery disease was studied selectively, mainly in males. In particular, published single reports of a decrease in total testosterone (TT) in men taking statins. Aim. To investigate the status of androgen support in patients with stable angina pectoris (SAP) in combination with type 2 diabetes mellitus (DM) and its modifications under the influence of statin treatment. Materials and methods. The effect of statin treatment on the indices of androgen availability of 120 SS patients in combination with DM type 2 on the basis of determination of the TT, testosterone-estradiol-binding globulin and free androgens index (FAI) was analyzed. Among the patients with SAP in combination with DM type 2, 53 (44.17 %) men and 67 (55.83 %) women. The average age of patients was 60.10 ± 0.78 years (57.85 ± 1.12 years – males and 61.88 ± 1.03 – females). SAP diagnostics were conducted in the accordance with the recommendations of the European Association of Cardiologists for the management of patients with stable coronary artery disease (2013), type 2 diabetes – the recommendations of the European Diabetes Policy Group and WHO (2011). Results. It demonstrates the definition of the levels of TT, testosterone-estradiol binding globulin (TEBG) in plasma and free androgen index calculation (FAI) = TT•100/TEВG. The androgen imbalance was studied and established that an average TT in men with SA in conjunction with type 2 DM was significantly reduced. It was determined that in women with SA and type 2 diabetes were increase both statins and FAI. In both men and women in the main group was established a decrease of TEВG in comparison with the control patients (p = 0.009 for men and p = 0.05 for women). The effect of the treatment with statins on the androgenic provision indicators was dose-dependent. Both men and women receiving high-dose statins showed a reduction in the average level of TT and FAI. In patients treated with statins in standard doses a significant impact on the androgenic provision indicators was not found (p > 0.05). Conclusions. In men with with type 2 DM, the SS passes with a decrease in TT level. The use of high doses of statins deepens the androgen deficiency (reduces the rates of TT and IVA). In women with DM, SS is accompanied by an increase in TT and IVA. The appointment of statins to patients with DM type 2 in combination with CC, corrects the androgenic imbalance.